MATH MODEL OF RUNNING INDEX FOR EVALUATION AND CONTROL OF SPECIFIC EFFICIENCY AND TRACING THE FATIGUE LEVEL IN LONG-DISTANCE RUNNING - Mihail Konchev; Dimcho Mitsov; Silvia Ilieva-Sinigerova (Journal of Applied Sports Sciences, 2022)
The aim of this case study was to develop and verify a math model of running index (RI) for evaluation and control of specific efficiency and tracing the fatigue level in long-distance running. The suggested RI was modeled on the basis of polynomial function between the running velocity and the change in heart rate frequency (V=f(HR)). The method was designed in such a way that the influence of denivelation of the terrain was removed when calculating RI. The research was done among 19 highly qualified athletes competing in long-distance running events (16 men and 3 women), with a mean age of 28 years (SD±8), BMI 20 (SD±2), maximum oxygen consumption 67 ml/min/kg (SD ±5). The participants in the research were subjected to two lab and two terrain surveys. In a period of one week after the testing, RI was traced and calculated on the basis of the data taken from the major training loads. The model was verified only for the studied subjects - highly qualified competitors in long-distance running. RI was tested for validity through comparing the values obtained from the lab and terrain tests. The obtained results showed there was no significant difference between the values of RI measured during the lab testing and the terrain testing compared to the values of the velocity of ventilatory and lactate anaerobic threshold (VAnT). The results from this research revealed that the suggested method for calculation of the running index is more accurate than the previous ones. This manuscript discusses the possible implications of this new method for measurement of RI. Future scientific research is needed to prove its efficiency and applicability in sport.